Otimização de solução extrativa e desenvolvimento tecnológico de produto seco por aspersão de Psidium guajava L. - Ferreira, Marcel da Silva (2009)
The increasing in the consumption of plant medicine by parts of the population generated a bigger need for studies. Drug substitutions, changes and adulterations at the production techniques are common places at plant-originated drugs trade, leading governmental departments of drug control round the world to adopt many analytical practices to medicinal plants. However, agronomic and technological issues cause characteristics and chemical composition variation at the drug, problem to be solved by the subject researchers. The present work aims to obtain a spray dried extract from a extractive solution obtained from Psidium guajava L. leaves based in book references that stress the intermediate dosage forms advantages. It also tries to validate useful methodologies for the quality control for both raw material and its derivates. Using eight sets of the spray dried extract (with Eudragit®, Aerosil ® e Avicel PH101 ® as drying adjuvants), the study proposes analytical methods using techniques commonly performed to plant medicines and its intermediate forms. As results, a viable spray-dried extract was obtained from a standartized extract solution. Among the studied adjuvants, the combination Aerosil ® with Eudragit ® showed the drying outcome, rheology, humidity and tannin content values that best fitted the demands of the Brazilian Pharmacopaea